Мультимедійні засоби у навчанні фаховому перекладу - Бадан, Антоніна Анатоліївна; Недайнова, Ірина Василівна (НТУ "ХПІ", 2017)
В даній статті відображено дослідження ефективності використання мультимедійних засобів у навчанні фаховому перекладу, що проводилося на кафедрі ділової іноземної мови та перекладу Національного технічного університету "Харківський політехнічний інститут" протягом останніх двох років. Висновки дослідження базуються на аналізі опитування як студентів так і викладачів кафедри щодо продуктивності застосування мультимедійних інструментів для вивчення англійської мови для професійних цілей.

This article concentrates on the opportunities that multimedia plays in the stages of second language acquisition for specific purposes. In Ukraine multimedia tools are being widely integrated into teaching English and this fact supports the implementation of high-quality instruction. At the same time, multimedia fosters new issues in higher education classroom. The paper reflects the research of multimedia efficiency at Business Foreign Language and Translation department at National Technical University “Kharkiv Polytechnic Institute” for the past two years. The conducted study is represented on the response-based analysis of using different multimedia tools in teaching English for specific purposes and involves both the teacherbased and student based analyses. Both the teacher’s mentoring and the student’s participation are being viewed and assessed in the multimedia enabled classroom as the counterpart contribution to the teaching process.
Multimedia means in teaching professional translation
Keywords: мова англійська; спілкування професійне; компетенції мовні; навчання аудиторне; технології мультимедійні; природа інтерактивна; ESP; language competences; classroom activities; multimedia technologies; interactive nature